2008
DOI: 10.1177/0145445508319668
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Excessive Media Usage While Increasing Physical Activity

Abstract: The Kaiser Family Foundation released a report entitled Kids and Media Use in the United States that concluded that children's use of media--including television, computers, Internet, video games, and phones--may be one of the primary contributor's to the poor fitness and obesity of many of today's adolescents. The present study examines the potential of increasing physical activity and decreasing media usage in a 14-year-old adolescent female by making time spent on the Internet and/or cell phone contingent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In the studies carried out in this area, it has been found that individuals who use the Internet in a general sense experience physical health problems involving the head, eyes, shoulder, neck, elbows, arms, wrist, forearms, hands and fingers, back and waist region, hips, feet and ankles). One study found that physical competences of users increased in one year when their Internet usage time was reduced (Larwin & Larwin, 2008). Psychosomatic symptoms, such as a lack of physical energy, physiological Volume 10 Number 4 2017 dysfunction and weak immunity (Cao, et al, 2011), caused by computer use for long hours, result from using the Internet for a long period of time in an inappropriate sitting position (Shields & Behrman, 2000), the formation of carpet tunnel syndrome in muscle groups (Shields & Behrman, 2000), the formation of health problems in the eyes, such as eye fatigue and eye irritation due to staring at a monitor for protracted periods (Subrahmanyam et al, 2000;Healy, et al, 2010), and increases in migraine pain (Suhail & Bargees, 2006) also negatively affect the individual in psychological and social terms, resulting in low self-esteem and the occurrence of occupational and personal disorders.…”
Section: Relationship Between Internet Addiction and Problem-solving mentioning
confidence: 99%
“…In the studies carried out in this area, it has been found that individuals who use the Internet in a general sense experience physical health problems involving the head, eyes, shoulder, neck, elbows, arms, wrist, forearms, hands and fingers, back and waist region, hips, feet and ankles). One study found that physical competences of users increased in one year when their Internet usage time was reduced (Larwin & Larwin, 2008). Psychosomatic symptoms, such as a lack of physical energy, physiological Volume 10 Number 4 2017 dysfunction and weak immunity (Cao, et al, 2011), caused by computer use for long hours, result from using the Internet for a long period of time in an inappropriate sitting position (Shields & Behrman, 2000), the formation of carpet tunnel syndrome in muscle groups (Shields & Behrman, 2000), the formation of health problems in the eyes, such as eye fatigue and eye irritation due to staring at a monitor for protracted periods (Subrahmanyam et al, 2000;Healy, et al, 2010), and increases in migraine pain (Suhail & Bargees, 2006) also negatively affect the individual in psychological and social terms, resulting in low self-esteem and the occurrence of occupational and personal disorders.…”
Section: Relationship Between Internet Addiction and Problem-solving mentioning
confidence: 99%
“…Although the current study was unable to identify a causal relationship, a significant association between increased screen time and reduced physical activity in HS may provide us with a hint for an effective solution. Indeed, in a 14‐year‐old female single‐case study, excessive media use was reported to have been successfully replaced by physical activity with the provision of a personalized, flexible, and detailed exercise program 42 . Interestingly, even 1 year after the cessation of the program, this girl's level of physical activity continued to increase, and her average Internet and cell phone use on non‐school days decreased to 1 h a day, compared to more than 1.6 h a day before participation in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Further, multiple agencies including the Centers for Disease Control (CDC) and U.S. Department of Health and Human Services as well as a growing body of research demonstrates that physical activity is critical to both improving academic outcomes for children but also to advancing their health [7,8]. While video games, TV, and other forms of screen time have been identified as factors in declining activity levels [9] other researchers are investigating exergaming as a way to get children to enjoy physical activity and increase their exercise motivation [10].…”
Section: Literature Review Physical Activity Of Childrenmentioning
confidence: 99%